2020
DOI: 10.1039/d0cp03511d
|View full text |Cite
|
Sign up to set email alerts
|

t1-Noise eliminated dipolar heteronuclear multiple-quantum coherence solid-state NMR spectroscopy

Abstract: Heteronuclear correlation (HETCOR) spectroscopy is one of the key tools in the arsenal of the solid-state NMR spectroscopist to probe spatial proximity between two different nuclei and enhance spectral resolution....

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 89 publications
(200 reference statements)
0
40
0
Order By: Relevance
“…The PT-D-HMQC MAS NMR spectra presented in this paper often suffer from marked t1 noise due to the strong dependence of the recoupling Hamiltonian rotor-phase on small fluctuations in the MAS frequency. In this respect, we note that various approaches to reduce t1 noise, for example based on using pi pulses to remove the CSA evolution during recoupling, have been introduced [60,73,74]. A 35 Cl  1 H double quantum (DQ) HMQC experiment, recently introduced by Hung et al [75], provides higher resolution for 35 Cl by reducing the second order quadrupolar broadening for a DQ coherence corresponding to the sum of the central transition and the satellite transition for the spin-3/2 35 Cl nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PT-D-HMQC MAS NMR spectra presented in this paper often suffer from marked t1 noise due to the strong dependence of the recoupling Hamiltonian rotor-phase on small fluctuations in the MAS frequency. In this respect, we note that various approaches to reduce t1 noise, for example based on using pi pulses to remove the CSA evolution during recoupling, have been introduced [60,73,74]. A 35 Cl  1 H double quantum (DQ) HMQC experiment, recently introduced by Hung et al [75], provides higher resolution for 35 Cl by reducing the second order quadrupolar broadening for a DQ coherence corresponding to the sum of the central transition and the satellite transition for the spin-3/2 35 Cl nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Venkatesh et al have previously observed such a suppression of the satellite transition peak using RAPT [32]. In the case that the 90 o pulses on 35 Cl are selective on the 35 Cl central transition, the signal from the 35 Cl satellite transitions would also be reduced [32,60]. Figure 3 presents comparisons of summed rows from the two-dimensional 35 Cl  1 H D-HMQC MAS NMR spectra of L-tyrosine•HCl.…”
Section: Evaluation Of 35 CL  1 H D-hmqc Mas Nmr Pulse Sequencesmentioning
confidence: 91%
“…The partial refocusing of the CSA 1H as well as the shorter delay between the CT-selective π/2 pulse and the maximum intensity of the spin echo, which is equal to τ 2 for PRESTO-III instead of 2jτ R (≥2τ 2 ) for PRESTO-II, can compensate for the magnetization loss due to the additional CT-selective π pulse applied to the S isotope in the case of the PRESTO-III variant. [38] It must be noted that using a phase inversion super cycle (e.g., R18 5 2 :R18 − 5 2 ) to increase the PRESTO robustness leads to a non γ-encoded sequence.…”
Section: Phase-shifted Recoupling Effects a Smooth Transfer Of Ordermentioning
confidence: 99%
“…This approach has already been employed to improve the efficiency of through-bond and through-space heteronuclear multiple-quantum coherence (HMQC) experiments involving half-integer quadrupolar isotopes in solids. [38,[58][59][60] 3 | NUMERICAL SIMULATIONS…”
Section: Refocused Ineptmentioning
confidence: 99%
See 1 more Smart Citation